2010
DOI: 10.4049/jimmunol.0903375
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of PI3K/Akt-Mediated Tumorigenic Signals through PTEN Activation by DNA Vaccine-Induced Anti-ErbB2 Antibodies

Abstract: By studying BALB/c mice deficient in immune components, we show that the protective immunity to rat ErbB2(+) tumors rests on the Ab response elicited by the electroporation of a DNA vaccine encoding the extracellular and transmembrane domains of rat ErbB2. In vivo, the adoptive transfer of vaccine-elicited anti-rat ErbB2 Abs protected against a challenge of rat ErbB2(+) carcinoma cells (TUBO cells). In vitro, such Abs inhibited TUBO cell growth by impairing cell cycle progression and inducing apoptosis. To cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…A previous study concluded that enhanced PI3K/Akt signaling induced by sodium orthovanadate treatment was attributable to inactivation of PTEN mediated by increased PTEN tyrosine phosphorylation (51). In addition, inhibition of PTEN tyrosine phosphorylation has been correlated with PTEN activation (32,38). Our current study obtained similar results which showed that IGF-I induced a significant increase in PTEN tyrosine phosphorylation that correlates with a reduction in PTEN activity in SMC, porcine endothelial cells, and preosteoblasts (MC3T3 cells).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A previous study concluded that enhanced PI3K/Akt signaling induced by sodium orthovanadate treatment was attributable to inactivation of PTEN mediated by increased PTEN tyrosine phosphorylation (51). In addition, inhibition of PTEN tyrosine phosphorylation has been correlated with PTEN activation (32,38). Our current study obtained similar results which showed that IGF-I induced a significant increase in PTEN tyrosine phosphorylation that correlates with a reduction in PTEN activity in SMC, porcine endothelial cells, and preosteoblasts (MC3T3 cells).…”
Section: Discussionsupporting
confidence: 83%
“…To identify a substrate of RPTP␤ whose change in tyrosine phosphorylation could alter IGF-I-stimulated AKT activation (21, 30), we focused on PTEN, since enhancement of tyrosine phosphorylation of PTEN decreases its enzymatic activity (38). IGF-I stimulated a 2.01-fold Ϯ 0.35-fold (mean Ϯ SE) increase in PTEN tyrosine phosphorylation that was further enhanced 1.5-fold Ϯ 0.3-fold by addition of IGFBP-2 with IGF-I (Fig.…”
Section: Fig 2 Knockdown Of Igfbp-2 Suppresses Rptp␤ Dimerization Andmentioning
confidence: 99%
“…However, the induction of anti-neu antibodies suggests that the inhibition of neu + TUBO tumors results from a synergistic action of anti-Amot antibodies targeting tumor vasculature and anti-neu antibodies that directly inhibit TUBO cell proliferation [38, 39]. An improved antitumor effect may stem from the combined reaction against endothelia and tumor antigens [8, 40].…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous data have shown that NK cells selectively kill CSCs derived from human colon carcinoma, 15 melanoma 16 and glioblastoma, 17 in mainly in vitro experiments. We herein describe in vitro and in vivo experiments which validate the NK cell targeting of breast tumor-derived CSCs using CSC-enriched tumorspheres 22 derived from an ErbB-2 C murine breast cancer tumor cell line (TUBO), 23 and murine and human triple negative breast cancer (TNBC) cell lines.…”
mentioning
confidence: 99%